Integration of Physical Education in the Merdeka Curriculum: A Literature Review on Holistic Approaches and Strengthening the Pancasila Student Profile - Doki Martadinata; Tri Bayu Norito; Hendri Munar; Reza Hadinata (Jurnal Pendidikan Jasmani (JPJ), 2026)
Physical education plays a strategic role in shaping the character, health, and social skills of students. In the context of implementing the Merdeka Curriculum, physical education not only functions as a physical activity but also as a means of developing the values of the Pancasila Student Profile, such as mutual cooperation, independence, and integrity. This article is a systematic literature review that aims to analyze the integration of physical education in the Merdeka Curriculum through a holistic approach. This study examines various national and international publications that discuss the relationship between physical education, character development, and curriculum innovation. The results of the review show that the application of a holistic approach in physical education can strengthen the cognitive, affective, and psychomotor dimensions of students in a balanced manner. In addition, physical education designed in accordance with the principles of the Merdeka Curriculum has the potential to increase learning motivation, awareness of healthy living, and collaboration among students. However, challenges are still found in the aspects of teacher competence, facilities, and authentic assessment. This study emphasizes the importance of synergy between curriculum policy, pedagogical innovation, and teacher training to achieve physical education goals that are in line with the values of the Pancasila Student Profile.